Bioinformatics Data-Based Lecture Modules on the Topic of Phanerogamae Diversity to Empower Student Research Skills - Zahro', Anisatuz; Muzzazinah; Ramli, Murni (LPPM Undiksha, 2024)
This research was motivated by the low level of research skills among students. At the same time, this skill is one of the competencies needed for academic and career success. This study aims to empower students' research skills using bioinformatics data-based modules, especially on Phanerogamae diversity. This study used mixed methods with an exploratory sequential design. The subjects involved in this study were 101 biology education students. Data was collected through interviews, document analysis, open-ended questions, and questionnaires. Data analysis used descriptive, paired sample T-test and N-Gain score. The results showed that the module proved feasible to use in lectures based on the assessment by material experts, media experts, and course practitioner lecturers. The developed module proved effective in empowering students' research skills with a significant difference between pre-test and post-test scores, and student responses to the module were positive. This study implies that the developed module can be an innovative teaching material in lectures to attract student interest in learning and accommodate research skills training.